Importance of Aflatoxins in Animal Feed - Kasturi Devi Kondampati; Beesam Srinu (The Indian Veterinary Journal, 2024)
Aflatoxins are the secondary metabolic products produced from moulds which have negative impact on animal health and production upon consumption. Majority of poor and developing countries with poor regulation authority in food processing, storage and weather condition as well as with high level malnutrition in all species of animals are susceptible to aflatoxicosis. Food and feed like groundnuts, sesame seeds, maize, millet and rice contaminations by aflatoxins have been reported due to fungal infection during pre- and post-harvest conditions. Even a low concentration of aflatoxins is hazardous for human and livestock. Aflatoxin B1 is the most common mycotoxin in food and among the most potent genotoxic and carcinogenic aflatoxins. It is produced both by Aspergillus flavus and Aspergillus parasiticus. Aflatoxin M1 is a major metabolite of aflatoxin B1 in humans and animals, which may be present in milk from animals fed with aflatoxin B1 contaminated feed. For effective food safety and quality, it is essential for identification and quantification of aflatoxins in food and feeds is a major challenge. Therefore, developing feasible, sensitive and robust analytical methods is paramount for the identification and quantification of aflatoxins present in low concentrations in food and feed. Diagnostic aids like chromatographic techniques viz HPLC, TLC and immunochemical detection methods for detection of aflatoxins in feed samples. The present review provides insights into effects of aflatoxin exposure on animal health, public health significance of aflatoxicosis, detection methods, prevention and control methods.